Molecular and Phylogenetic Characterization of Infectious Bursal Disease Virus Re-emerging in Backyard Poultry in Pakistan: IBD Virus Re-emergence in Pakistan - Ahmad, MT; Aiman , UE; Sarfraz , MT; Bhutta, ZA (Journal of the Hellenic Veterinary Medical Society, 2026)
In recent periods, Infectious bursal disease (IBD) has re-emerged with virulent strains, resulting in significant losses to the economy of Pakistan. IBD is caused by a virus of the species Avibirna, causing severe immune suppression, and accompanying other secondary infections. A total of one hundred and ten birds were selected with a history of IBD infection from three different government diagnostic labs and private farms. After the necropsy, the samples were processed for histopathology, and only selected positive samples from histopathology were processed for molecular detection and phylogenetic analysis. According to our findings, the bursa of Fabricius during the necropsy was edematous, hemorrhagic, and enlarged in size, along with haemorrhages on the pectoral muscles and the gizzard and proventriculus junction. The histopathological examinations of 20 samples revealed that the virus severely affected the bursa as there were atrophic, necrotic changes, increased interfollicular spaces, and replacement of fibrous cells. Then 12 samples were confirmed through RT-PCR by amplifying HVR-VP2. The samples were sequenced to analyze the nucleotide sequence of the IBD virus, referring to ‘‘UVAS-01’’ as a predominant, virulent strain from the samples obtained from the backyard poultry. The obtained data from the sequence were analyzed with the reported strains of Pakistan and other parts of the world. The similarity index for ‘‘UVAS-1’’ was 98-100% with the reported vvIBDV strains in Pakistan, while there was a 92-100 % identity index for the very virulent strains prevalent in other regions of the globe. Through phylogenic trees, it was first identified vvIBDV strain in the southeast part of Punjab, Pakistan, in the backyard poultry. Further work is required to study the reassortment in local strains for the emergence of vvIBD in indigenous breed farming.